EFEKTIFITAS PENYULUHAN PENCEGAHAN OSTEOPOROSIS UNTUK MENINGKATKAN PENGETAHUAN WANITA USIA SUBUR DI DESA RAMBAH TENGAH HILIR - Rahmi Fitria; Eka Yuli Handayani (Jurnal Ilmu Kebidanan, 2022)
Osteoporosis or calcification of bones is a symptom that can occur in postmenopausal women. Bones with osteoporosis will become hollow, causing easy fractures. Risk factors for osteoporosis can be hormonal, calcium intake, gender, vitamin D, physical activity, caffeine consumption, alcohol consumption, blood sugar levels, hypertension, long-term use of corticosteroids, parity, nutritional status and duration of menopause. The population of this study were women of childbearing age, and the sample was 103 women of childbearing age using simple random sampling technique. Pre-experimental quantitative analytical research method with one group pre-post design.